Requirements for the contents and evaluation of scientifically oriented Bachelor's projects in Bachelor of Science programs for occupational and physical therapists. - Fischer A (pt Zeitschrift für Physiotherapeuten, 2005)
We describe here the criteria which need to be considered when evaluating scientifically researched Bachelor's theses. We used two approaches to establish these criteria. The first was to analyse the basic European and German situation from the point of view of social and higher education politics, as they influence three-stage academic education, including Bachelor's, Master's, and Doctoral degrees. In order to do this, we used as a point of reference the current guidelines set forth by both the conference of the ministry of culture and the accreditation advisors, as well as recommendations of the central evaluation and accreditation office of the State of Lower Saxony. The second was to examine the standards and requirements which were set up in the European and Anglo-Saxon regions for the structure, content, and implementation of Bachelor's programs as well as the competencies and role models expected from graduates of such programs. In particular, the recommendations of the European Network of Occupational Therapists in Higher Education as well as the guidelines and recommendations of the American Occupational Therapy Association, the American Occupational Therapy Foundation as well as the Accreditation Council on Occupational Therapy Education were taken into account.